VAGrENT: Variation Annotation Generator. Issue 1 (17th December 2015) - Menzies, Andy; Teague, Jon W.; Butler, Adam P.; Davies, Helen; Tarpey, Patrick; Nik‐Zainal, Serena; Campbell, Peter J.
Abstract: VAGrENT is a tool that provides biological context and effect prediction for genomic sequence variants. It annotates single base substitutions and small insertions and deletions by comparing them to reference information within or close to genes or other transcribed elements. This information provides the critical insight required to inform the biological or clinical significance of variant data generated from sequencing studies. The software has been optimized to run efficiently against the large numbers and diverse classes of variants that are typically generated from next generation sequencing technologies. This unit describes how to configure and use VAGrENT and also contains support protocols for extending and adapting its default behavior. © 2015 by John Wiley & Sons, Inc.